Tinjauan Hukum Wali Pengampu Bagi Ahli Waris Cacat Mental dalam Sengketa Waris di Pengadilan Agama Kabupaten Kediri - Fatmah; Ahmad Faisal Fahrurudin (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This study investigates the role of guardians in handling inheritance disputes involving mentally disabled heirs at the Kediri District Religious Court. By referring to the views and teachings of Imam Syafi'i, this study attempts to understand the Islamic view of legal protection for individuals with mental disabilities in the context of the inheritance law. The research method used in this study involves analyzing legal documents, interviewing Islamic legal experts, and tracing related legal cases. The results of this study illustrate the important role of guardians in safeguarding the rights of mentally disabled heirs, including the process of inheritance distribution and related legal decisions. This study also discusses the extent to which Imam Syafi'i's perspective is reflected in the practice of inheritance law at the Kediri District Religious Court. The results strengthen the understanding of the importance of legal protection for individuals with mental disabilities in the Islamic legal system as well as how religious teachings can be applied in the context of inheritance law, where conflicts within the family are avoided. This research is expected to provide a better view of legal protection for individuals with mental disabilities in inheritance disputes in Indonesia, particularly in Kediri District. The implications of this research can be the basis for improvements in the practice of inheritance law and the protection of the rights of vulnerable individuals in the Islamic legal system.